Nitrogen availability in grain sorghum under Cerrado conditions (Research, Society and Development, 2022)
The objective was to evaluate the effect of the addition of increasing doses of nitrogen (N) in grain sorghum on development in sandy textured soil with low fertility in Cerrado conditions. The work was carried out at Fazenda Pântano located, in the municipality of Jataí – Goiás, Brasil. The seeds used for the experiment were the AG 1085 variety. Using five doses of N: 0 (control), 50, 100, 150 and 200 kg ha-1, the source being urea, with five replications each, with a design in randomized blocks, totaling 25 experimental units. The variables evaluated were: stem length (CC), stem diameter (DC), leaf area (AF), shoot dry mass (DM), leaf nitrogen content (TN), nutrient accumulation (AC), nitrogen efficiency (NE), chlorophyll A (CLA) and chlorophyll B (CLB). The different doses of N had a significant effect for all variables except for the nitrogen content in the leaf, chlorophyll A (CLA) and chlorophyll B (CLB) contents. The dose indicated for the best development of the grain sorghum crop in the low fertility conditions studied was 150 kg-1 of N per hectare.